Commercial coral-reef fisheries across Micronesia: A need for improving management - Houk, P.; Rhodes, K.; Cuetos-Bueno, J.; Lindfield, S.; Fread, V.; McIlwain, Jennifer (Springer Verlag, 2012)
A dearth of scientific data surrounding Micronesia’s coral-reef fisheries has limited their formal assessment and continues to hinder local and regional management efforts. We approach this problem by comparing catch-based datasets from market landings across Micronesia to evaluate fishery status in the Commonwealth of the Northern Mariana Islands (CNMI), Guam, Yap, and Pohnpei. Initial examinations found that calm weather and low lunar illumination predicted between 6% (Yap) and 30% (CNMI) of the variances in daily commercial landings. Both environmentally driven catch success and daily catch variability increased in accordance with reef-fish demand indices. Subsequent insight from species composition and size-at-capture data supported these findings, highlighting reduced trophic levels and capture sizes where higher human-population-per-reef-area existed. Among the 12–15 target species and/or species complexes that accounted for 70% of the harvest biomass, capture sizes were consistently smallest for CNMI and Guam, often below the reported mean reproductive sizes. Comparatively, Pohnpei has the greatest potential for reef fisheries, with a large reef area (303 km2) and a moderate human population (34,000 people).However, the estimated harvest volume of 476 mt year−1 was 8–9 times higher than other jurisdictions. Even on Yap where the reef-fish demand index was lowest (67.7 people km−2 reef habitat), many target fish were harvested below their mean reproductive sizes, including the iconic green bumphead parrotfish and humphead wrasse, as well as several other herbivores. We discuss our results with respect to the contemporary doctrine surrounding size-spectra, catch composition, and catch frequencies that afford insight into fishery pressure and status. We posit that regional catch-based policies (initially) instituted at the market level, combined with area and gear-based restrictions, represent plausible vectors for improving Micronesian fisheries.